OPPORTUNITIES FOR DEVELOPING FUTURE TEACHER COMPETENCE IN THE PROCESS OF TEACHING NATURAL SCIENCES - Erdanayeva Shahnoza Po’latovna (Modern American Journals, 2025)
The article emphasizes that the reform and modernization of education requires innovative, systematic, proactive, creative approaches in teaching students environmental and pedagogical thinking in organizing the process of higher pedagogical education. It also ensures the consistent development of environmental competencies of future teachers, which reflects the specifics of a systematic approach to the development of environmental competencies.
Keywords: students, education, ecology, competence, development, systematic approach.